Short-and long-term exposure to heavy metals induced oxidative stress response in Pseudokirchneriella subcapitata - Machado, Manuela D. (2016)
Algal cells can be exposed to toxicants for a short term due to accidental discharges or, more commonly, for a long term. The present work aimed to assess the ability of Cd, Cr, Cu and Zn to induce accumulation of reactive oxygen species (ROS) in the alga Pseudokirchneriella subcapitata after a short (6?h) or a long (72?h) exposure time. The relationship between the ROS induction and the content of reduced glutathione (GSH) was also examined. For this purpose, three nominal concentrations of each metal were used corresponding approximately to 72 h-EC10 and 72 h-EC50 values and a high concentration (>72 h-EC90 values). Intracellular ROS accumulation and GSH content were evaluated using a fluorescent-based approach. A long-term (chronic) exposure of algal cells to Cd, Cu and Zn, at the highest concentrations tested, induced an increase of intracellular ROS and GSH content. The increase of GSH content might be a form of algal cells to redress the imbalance caused by the oxidative stress. However, the increase of GSH was not enough to protect the algal cells against the long-term exposure to oxidative stress. The exposure of algal cells to low or intermediate metals concentrations induced a modification of GSH content; however, no increase of ROS production was detected, which indicates that the toxic symptoms exhibited by algal cells, under these conditions, cannot be attributed to intracellular ROS accumulation.